The Impact of Digital Surveillance, Social Media Exposure, and Workplace Stress on Employee Mental Well-being: The Mediating Role of Work-Life Balance - Arooj Fatima; Laraib Khan; Alina Raza (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
In an era of increasing digitalization, this study examines the impact of digital surveillance, social media exposure, and workplace stress on employee mental well-being, with work-life balance as a mediating factor. Rooted in Workplace Stress Theory and the Job Demands-Resources (JD-R) Model, the research explores how digital monitoring and excessive online engagement contribute to psychological distress in modern workplaces. By addressing these challenges, the study provides insights into organizational control, digital dependency, and employee well-being. A quantitative research design was employed, with data collected from 500 employees across various industries in Pakistan. Using Structural Equation Modeling (SEM), the study assessed direct and indirect relationships between key variables, highlighting the mediating role of work-life balance in reducing workplace stressors. The results reveal that excessive digital surveillance and prolonged social media exposure significantly increase workplace stress, leading to anxiety, emotional exhaustion, and declining mental well-being. This study contributes to the growing discourse on workplace digitalization and occupational health, emphasizing the urgent need for organizations to regulate excessive monitoring, implement digital detox policies, and promote work-life balance initiatives